ECONOMIC AND FINANCIAL INDICATORS OF THE HIGHER EDUCATION SYSTEM: EXPERIENCE OF UKRAINE, POLAND AND GERMANY - Lisun, Yanina; Tarasenko, Iryna; Pochopień, Jolanta (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The article is devoted to a comparative analysis of the main economic and financial indicators of the functioning of higher education in such countries as Ukraine, Poland, and Germany for the period 2010-2021. Considering the military aggression against Ukraine and the assistance of the specified neighboring states, such monitoring of statistical data is useful and can serve as a basis for further forecasts regarding the development of the higher education system in Europe. Although in the modern conditions of the multi-system crisis in Ukraine, any forecasting is a rather difficult matter. The main trends regarding the number of higher education institutions, the number of students and teachers, as the basic factors determining the effectiveness of the functioning of the higher education system in Ukraine, Poland and Germany, were determined. The article uses official statistical data from the State Statistics Service of Ukraine, Statistics Poland, and the German Federal Statistical Office. The following indicators of financial policy in the education sector were analyzed, such as: budget expenditures in the education sector; Total balance sheet of enterprises in the education sector; financial results in the education sector; profitability of operating activities of the HEI; costs per student.